The Agro Pontino, climate change and malaria (Italian Journal of Public Health, 2009)
Recently in Italy a case of malaria was reported (November 2009). The patient was an Italian man of 44 years of age who had not travelled out of the country. The man apparently contracted malaria during a 2 weeks stay in August 2009 in a former malaria endemic area, the “Agro Pontino” (60-100 km South of Rome). Although confirmation of the Plasmodium species and the results of the epidemiological investigation undertaken by the Ministry of Health are still not available, the case seems unlikely to be linked with accidental contact of the patient with imported vectors or contaminated blood. This case raised concern over the possible recrudescence of malaria in Italy, especially in light of current and future climate change. Given the importance of the topic, this article will provide a brief review of the history of malaria in the Agro Pontino and the recent discussions that have appeared in scientific journals concerning the link between malaria and climate change.